FACTORS ASSOCIATED WITH PREVALENCE OF HYPERTENSION AMONG ADULTS AGED 30-79 YEARS ATTENDING THE HYPERTENSION CLINIC AT HOIMA REGIONAL REFERRAL HOSPITAL. A CROSS-SECTIONAL STUDY. - Caroline Nabukalu (Student's Journal of Health Research, 2023)
Background: Hypertension also known as High or Raised blood pressure is a condition in which the blood vessels have persistently elevated blood pressure. This study, therefore aimed at assessing factors associated with the prevalence of hypertension among adults aged 30-79 years attending the hypertension clinic at Hoima Regional Referral Hospital. Methodology: A cross-sectional study design was employed involving both qualitative and quantitative methods of data collection. Kish and Leslie's method was used in determining the sample size of 75 respondents who were obtained by simple random sampling technique. Results: The majority 27(30%) of the respondents with hypertension were aged 60-69 years followed by 20(26.7%) aged 50-59 years, 50(86.7%) were females, 35(46.7%) attained at most primary level of education while 20(26.7%) had no formal education and 48(64%) were living in rural areas. Furthermore, the majority 70(93%) of the respondents did not smoke a cigarette or have a history of cigarette smoking, more than half 40(61.5%) regularly ate vegetables more than 3 times a week, 52(69.3%) did not take alcohol, 72(96%) agreed to stress increasing one's chances of developing hypertension and 28(37.4%) were classified as being overweight while 27(36%) were obese. There was no significant difference between participants having a relative with hypertension and those who did not. 50(66.7%) identified stress as a risk factor for hypertension while the rest of the risk factors were known to a few of the participants. Knowledge regarding the signs and symptoms of hypertension was good and health workers 45(60%) were identified as the major source from which the respondents had ever first got to hear about hypertension. Conclusion: The overall level of knowledge about hypertension among the respondents was average. Recommendations: The government in conjunction with the administration and health workers at HRRH should organize regular and comprehensive health education programs and campaigns regarding hypertension.